2015
DOI: 10.1155/2015/179426
|View full text |Cite
|
Sign up to set email alerts
|

ArtemisiaAllergy Research in China

Abstract: Artemisia is the most important outdoor allergen throughout China. It can cause allergic rhinitis, asthma, or both of them. Since it was verified as an allergenic pollen in 1960, it was identified two times in the Chinese National Pollen Survey (1984, 2009). The first oral immunotherapy double-blinded trial for Artemisia pollen asthma research was conducted in China in 1989 and published in 1990. 40 years since that study, there have been many published research reports on Chinese Artemisia allergy. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…Although the prevalence of 66% in SX is quite similar to that reported in central Europe, IgE levels are much higher. The striking difference between SX and SD is most likely explained by a higher pollen load in SX and possibly by different Artemisia species dominating in the regions . Art ar 2 had the least prevalence (42%‐48%) and IgE levels, being close to the 58% for Art v 2 reported in Europe …”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Although the prevalence of 66% in SX is quite similar to that reported in central Europe, IgE levels are much higher. The striking difference between SX and SD is most likely explained by a higher pollen load in SX and possibly by different Artemisia species dominating in the regions . Art ar 2 had the least prevalence (42%‐48%) and IgE levels, being close to the 58% for Art v 2 reported in Europe …”
Section: Discussionmentioning
confidence: 74%
“…A cross‐sectional study has shown that overall, while about 11.3% of patients in China with respiratory allergies are sensitized to Artemisia pollen, this value is much higher in Northern China (>50%). Among the major pollen species causing seasonal allergic asthma in China, Artemisia pollen has the highest association index . The hop ( Humulus scandens ) , ragweed ( Ambrosia artemisiifolia ), and goosefoot ( Chenopodium album ) pollen seasons overlap with that of Artemisia , but their IgE positive rate was significantly lower in a survey of a large number of ImmunoCAP tests in Beijing .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the different allergenicities among pollens, frequent rain in this area also restricts the spread of pollens. In contrast, the dry, windy, and rainless climate in Northern China leads to the epidemic of pollinosis [21]. Similar to other regions, mold sensitization is usually less common than mite and pollen causes [22].…”
Section: Discussionmentioning
confidence: 99%
“…Artemisia pollens have been recognized as a major cause for late summer and autumn seasonal allergic respiratory disease worldwide, particularly in China, north of the Yangzi river [1]. Molecular characterization of Artemisia pollen allergens has revealed 7 protein molecules [2].…”
Section: Introductionmentioning
confidence: 99%